International law applicable to the oceans: the fourth decade of the United Nations Convention on the law of the sea - Campos Maza, Gian Pierre (2023)
The United Nations Convention on the Law of the Sea, four decades after the adoption of its final text, has become the main source of the law of the sea applicable to human activities in the ocean. The almost planetary recognition and the almost indisputable validity of the Convention is based on its successful capacity to regulate the rights and obligations of the States in the maritime spaces established by it, as well as on its aptitude to adapt to the new realities and problems that the oceans face. Based on the analysis of the Convention, it seeks to understand the mechanisms that allow it to respond to the needs and interests of an international system in permanent change.